IMPLEMENTASI MODEL PEMBELAJARAN MATEMATIKA TIPE JIGSAW UNTUK PEROLEHAN BELAJAR BANGUN RUANG DI SMP NEGERI 1 TUMBANG TITI - yarso, Syaidianur; Aunurrahman, Aunurrahman; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find: 1.) Design of jigsaw type mathematics learning model for learning to build up space in class IX Tumbang Titi Junior High School 1. 2.) Steps of jigsaw type learning model for learning to build up space in class IX junior high school Negeri 1 Tumbang Titi. 3.) Differences in the acquisition of wake-up learning space on cognitive and affective aspects, using jigsaw type mathematics learning models and those using conventional learning in class IX Tumbang Titi Junior High School 1. The research method used in this study is concurrent embedded design. Concurrent embedded design is a research method that combines the use of quantitative and qualitative research methods simultaneously or together but the weight of the method is different. The selection of the use of research methods of mixed methods of concurrent embedded design is because the researcher considers that this approach is very appropriate to be used in research that researchers do. The results of the study are: 1.) Jigsaw Type Mathematics Learning Model Design for Acquiring Learning to Build Space. 2.) Implementation of Jigsaw Type Mathematics Learning Model. 3.) Student Learning Acquisition in Jigsaw Type Mathematics LearningÂ Keywords: Implementation, Learning Model, Learning Acquisition